Low-dose ionizing radiation and the exposure–lag response: protocol for a prospective cohort study on The Health Effects of Chongqing Occupational Radiation Workers - Qin, Xiao-Ling; Huang, Qiang; Zhang, Han-Wen; Zeng, Yi; Lin, Xian-Shu; Fan, Xiao-Yuan; Diao, Jun; Chen, Cheng-Zhi; Cheng, Shu-Qun; Yuan, Fang; He, Jun-Lin; Li, Wei; et al. (Frontiers in Public Health, 2025)
IntroductionAlthough the effects of ionizing radiation on radiation workers have been extensively studied in China, no prospective cohort study has been conducted in Chongqing. Furthermore, previous cohorts have not provided a broad-gauge assessment of the temporal relationship between low-dose occupational radiation exposure and the risk of health outcomes.MethodsA prospective cohort study will be carried out focusing on radiation workers in Chongqing. Health examination outcomes and radiation dose monitoring data will be collected and analyzed using the distributed lag non-linear model (DLNM) combined with generalized additive model (GAM) or generalized linear model (GLM) to evaluate the exposure-lag response relationship.DiscussionOur study will enhance our understanding of the exposure-lag response association between occupational radiation exposure and the health of radiation workers based on DLNM.Clinical trial registrationChinese Clinical Trials Registry, ChiCTR2400081804.